BRMS1L promotes chemotherapy sensitivity by inhibiting autophagy in breast cancer - Li, Yuan; Zhang, Dian; Zhao, Junhao; Yang, Mei; Wang, Yiping; Lee, Peiyao; Qu, Shaohua (Frontiers in Genetics, 2025)
Chemoresistance remains a crucial obstacle in breast cancer therapy. The mechanisms underlying chemoresistance need to be explored urgently and in depth. Breast cancer metastasis suppressor 1 like (BRMS1L), a core component of the Sin3A–histone deacetylase (HDAC) co-repressor complex, has been reported to suppress breast cancer metastasis through epigenetically regulating the Wnt signal pathway. However, whether BRMS1L could regulate chemosensitivity has not been explored. Herein, we found that higher BRMS1L expression was significantly correlated with increased chemotherapy sensitivity and better prognosis in patients receiving neoadjuvant chemotherapy. In vitro experiments confirmed that chemoresistant breast cancer cells exhibited decreased BRMS1L expression compared to chemosensitive cells. In vivo experiments in nude mice demonstrated that BRMS1L markedly strengthened the chemotherapy effects on xenografts. RNA sequencing (RNA-seq) was performed to elucidate the molecular mechanism underlying BRMS1L-mediated chemosensitivity. Bioinformatics analysis indicated that BRMS1L promotes chemotherapy sensitivity by regulating cellular autophagy. Furthermore, chemoresistant breast cancer cells exhibited elevated autophagy levels, and ectopic expression of BRMS1L significantly suppressed protective autophagy through downregulating ATG5. Collectively, these results revealed that BRMS1L enhances chemotherapy sensitivity via inhibiting protective autophagy. To our knowledge, this is the first study that showed that reduced BRMS1L expression is associated with poor response to neoadjuvant chemotherapy and unfavorable prognosis in breast cancer patients. Our findings reveal a novel role of BRMS1L in chemosensitivity and highlight its potential clinical application in the treatment of breast cancer.